A CLINICAL STUDY ON THE EFFECT OF UTKLESHANA, DOSHAHARA AND SAMSHAMANA VASTI IN THE MANAGEMENT OF AMAVATA (International Journal of Ayurveda and Pharma Research, 2016)
Basti Chikitsakarma is one of supreme therapy for the elimination of vitiated Vatadosha and has entity to entice all Doshas. In the present clinical practice with the reference of Acharya Sushruta, the scientific application of Utkleshana, Doshaharaand Samshana Vasti has an approach towards Datugatadoshaharana in all aspects of diseases. Among them one of the most crippling, disabling and debilitating disorder is Amavata. So looking to the etiopathogenesis of Amavata, it shows a Bahudoshayuktavyadhi mainly involvement Vata, Kaphadoshas and a part of Pitta predominantly. Its Udbhavasthana in Ama Pakwashaya, Sancharasthana in Rasavaha and annavahasrotas, Adhistana and Vyktasthana are Kaphasthana like AmashayaSandhi etc. As it is a Kastasadhyaswabhava, it needs a complete inclusive treatment. In that view the application of Utkleshanabasti, followed by Doshaharabasti and finally Samshamanabasti is selected.A total of 30 patients presenting with symptomatology of Amavata were simple randomly selected for study. The study design, schedule, duration and follow-up of the treatment have clearly explained. Subjective and objective criterias were statistically analyzed before and after treatment by applied standard statistical method. All subjective and objective parameters showed highly substantial significant result of 73.33% and 80.28 mean grade result found among 22 patients out of 30 Amavata patients and a high significant fair result of 26.66% and 71.96 mean grade result found among 08 patients out of 30 Amavata patients. The overall assessment mean result was 76.12 in both subjective and objective parameters were observed.